Pengaruh Kebiasaan Belajar, Lingkungan Belajar Dan Motivasi Belajar Terhadap Prestasi Belajar Siswa MTS Darul Hikmah Langkap Burneh Bangkalan - Amrulloh, Amrulloh; Aliyah, Nelud darajaatul; Darmawan, Didit (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Education plays a crucial role in shaping students' characters and unlocking their potential. At the secondary level, factors influencing student achievement are of paramount concern. Academic success hinges not only on internal factors like study habits but also on external factors such as the learning environment. This study aims to assess how study habits and the learning environment impact student achievement at MTs Darul Hikmah Langkap Burneh Bangkalan. Employing a quantitative approach with regression analysis, the research encompassed all students at the school, with a randomly stratified sample of 30 participants. Analysis involved descriptive statistics and regression techniques, revealing that strong study habits significantly correlate with higher academic performance. Moreover, a conducive learning environment and positive social interactions also contribute positively to academic success. These insights are expected to inform the development of more effective educational initiatives